EDUCATION OF ENDURANCE - AGILITY OF THE WRESTLER - Akhtamov Jamshed Bahromovich (Journals Park Publishing, 2023)
In this article performing exercises to develop strength, popularizing physical education and sports, it was discussed about the strength of the wrestler without increasing his weight, the ability of the body to withstand fatigue and restore the work ability after the increase, the high level of development of physical training and the wealth of technical methods.
Keywords: keeping the muscles unchanged, the possibility of advantage over the opponent, developing strength, within the scope of the opportunity, with a large load, highly qualified athletes, developing strength, the basic structure of the movement technique, exercises performed with a partner.